Frozen Spring Rolls / Wan Farhana Wan Azraimizam - Wan Azraimizam, Wan Farhana (2021)
This written report that has given required to conduct a business activity either sells the product or offer services. This overall report is designed to describe the business that runs by the entrepreneur for the past 3 weeks. It also included the overview of the business as much as the product that offered, where did the business was conducted, the business target, etc. Additionally, it also included the process of the business that has been conducted as much as the operation of the business. The business activity that I conducted was a small business that sell frozen spring rolls. It was a really big challenge for me to do this activity as it is the first time, I am conducting the business. With passion and persistence, the overall business activity that was conducted was great. In order to get the customers, I need to promote and advertise the product to the people. Along with the growth of the online market, I took this opportunity to try out managing the business online. There are several problems that I encountered during working on this project. At the beginning of this activity, I need to find a suitable business that fulfil the customer’s needs. It was really hard to decide on something that I can sell in order to complete this activity. I also face the problem regarding my laptop that always lagging and it always not responding. In general, I would say that this business activity really gave me the opportunity to learn and gain knowledge about the business even though I encountered many problem